(untitled) (Review of Croatian History, 2022)
By taking advantage of abundant literature that has been written on the subject, the paper aims to give an overview of the history of rock music in Yugoslavia from its introduction in 1956 to the mid-1970s, when the new wave emerged. It also intends to remind the reader of this topic’s relevance and open possible new research questions for history and related fields. Particular emphasis will be placed on the impact that this musical, cultural, social, and political phenomenon had on the lives of Yugoslav and other socialist youth while highlighting the changes rock’n’roll brought to their lives, including opening up to Western cultural influences through new fashion, different forms of youth entertainment, new understanding and redefining of gender relations. Also, the paper will review the cooperation of Yugoslav rock musicians with the Eastern bloc musicians. Through the analysis of articles found in Džuboks, a youth music magazine deemed popular at the time. The paper will attempt to illustrate how the Yugoslav youth rock press helped shape the minds of young people. This paper intends to remind the reader of this topic’s relevance and open possible new research questions for this and related fields.